Assessment of the state of conservation of a Middle Neolithic flint mine in Maastricht limestone, Valkenburg (Limburg) (Bulletin KNOB, 2009)
Upper Cretaceous Maastricht limestone (locally denominated as ‘mergel’) outcrops in the provinces of Dutch and Belgian Limburg. The Upper Cretaceous in the Netherlands consists of the geological Maastricht Formation and the upper part of the Gulpen Formation. Limestone from the Maastricht Formation represents one of the few native Dutch types of natural stone used for building and construction. Locally, limestone from both formations contains considerable amounts of flint. This flint was mined in Neolithic times, both from the Lanaye limestone in the Gulpen Formation and the Emael Limestone in the Maastricht Formation. Flint from the South Limburg province was used for tools in a major part of north-west Europe. Around the village of Valkenburg aan de Geul, flint was mined from the Emael limestone. The originally subsurface mine, which had become exposed due to excavation of the valley slope in the past, was discovered in the 1990s. In the current study, the state of conservation of a Middle Neolithic flint mine situated at Plenkertweg in Valkenburg aan de Geul is assessed, eight years after the site was discovered. The assessment is based on determination of hydric behaviour and petrographic investigation of Maastricht limestone from the outcrop, and analysis of moisture conditions of the outcrop itself.